PENGARUH KREDIT MACET USAHA MAKRO TERHADAP TINGKAT PEROLEHAN LABA PADA PT. BANK LAMPUNG - Rahayu, Mieke (Jurnal Manajemen dan Keuangan, 2008)
PT Bank Lampung is one of the Bank in Province Lampung and growth of credit stuck macro effort experience of improvement, while acquirement of downhill profit. Pursuant to problems, hence becoming this research internal issue formula is how big of interest income and credit stuck macro effort have an effect on significant to level acquirement of profit. Target of this research is to measure influence of interest income and credit stuck macro effort to level acquirement of profitThis research is conducted by using quantitative analysis with method calculation of doubled linear regression, sample the used is credit data stuck macro effort, interest income and also profit report or loss period of year 2003-2007 and also with doubled linear method will be able to be conducted by examination of his hypothesisResult of this research indicate that pursuant to calculation obtained by F calculate equal to 14,467> Table F = 19,00 or significant 0,002>0,05 there by Ho refused on the contrary is Ha accepted. Equally there is influence by significant between interest income and credit stuck to level acquirement of profit. Test t for the significant test of and constant of variable interest income independent and credit stuck macro effort if seen from interest income equal to 0,001< 0,05 so Ho refused and is Ha accepted. Mean influence of interest income to profit very significant. If seen from credit stuck macro effort of probability significant equal to 0,019 < 0,05 so still there are influence between credit stuck macro effort to level acquirement of profit at PT Bank Lampung in Bandar Lampung.Pursuant to breakdown of above hence can know that Coefficient of regression for the interest income of (X1) equal to 13,34, please express that each addition one set of (X) hence will improve level acquirement of profit (Y) equal to 13,34. Coefficient of Regression for credit stuck macro effort (X2) equal to -1,07 expressing that each reduction one set of X hence will degrade level acquirement of profit ( Y) equal to -1,07.Keyword: Interest Income, Credit Stuck the Effort Macro, level acquirement of Profit.